Post-annealing in ultra-high vacuum or nitrogen plasma for MoS2 thin films deposited by magnetron sputtering - Chih Chao; Ping-Yu Tsai; Po-Hung Wu; Ray-Yu Hong; Ing-Song Yu (AIP Advances, 2024)
The thin films of amorphous molybdenum disulfide were deposited at room temperature by magnetron sputtering technique. Post-annealing process in ultra-high vacuum (∼10−8 Pa) or nitrogen plasma environments at the temperatures of 300, 400, 500, and 700 °C have been first proposed to enhance the microstructure and optical properties of MoS2 thin films. The phase transformation of MoS2 thin films from amorphous to polycrystalline was characterized by in situ reflection high-energy electron diffraction during the post-annealing process. The microstructure of MoS2 thin films was also analyzed by Raman spectrum and X-ray diffractometer after the post-annealing process. In addition, the thermal analysis of the differential scanning calorimeter and optical measurement of photoreflectance confirmed the phase transformation of MoS2 thin films. The analysis of photoreflectance also estimated the exciton transition at the bandgap energy of 2.038 eV at 0 K, attributed by the crystalline MoS2 film annealed at 700 °C in ultra-high vacuum. The surface chemical composition of MoS2 thin films has been identified by X-ray photoelectron spectroscopy, but the desulfurization of MoS2 was observed after post-annealing in ultra-high vacuum. Moreover, the preferred orientation of (004) plane in the MoS2 films was performed as the increase in post-annealing temperature.